Comparative analysis of precision, deficit, and drip irrigation for water efficiency in Iraq - Jumintono Jumintono; Nurnawaty Nurnawaty; Nugroho T. Brata; Dini Rahmiati; Hadi Susilo; Ahmad Hussen (Journal of Water and Land Development)
Sustainable irrigation practices are critical for addressing the challenges of water scarcity and food insecurity in the face of climate change and growing global food demand. This study investigated the potential of precision irrigation (PI), deficit irrigation (DI), and drip irrigation (DRI) techniques to enhance crop productivity and water use efficiency (WUE) compared to conventional flood irrigation (CFI) in three distinct agroecological zones of Iraq. Field experiments were conducted using a randomised complete block design with wheat, maize, and rice crops. The results demonstrated that PI significantly increased crop growth parameters, grain yield, and WUE across all zones, with yield improvements of 33–38% and WUE increases of 46–51% in contrast with CFI. The DI and DRI treatments also outperformed CFI, albeit to a lesser extent. Remote sensing-derived vegetation indices strongly correlated with crop growth parameters and yield, while hydrological modelling revealed reduced evapotranspiration and surface runoff under the PI treatment. The sustainable irrigation practices resulted in substantial water savings of 20–30% compared to CFI. These findings highlight the importance of adopting efficient irrigation techniques, along with a holistic approach encompassing technological innovations, capacity building, and stakeholder engagement, to promote water- efficient agriculture and ensure food security in water-scarce regions.